Elaboration of an algorithm for preserving a projective skin flap above the tumor when planning subcutaneous mastectomy from an aesthetically acceptable area in patients with breast nodule cancer - A. R. Khamitov; A. Kh. Ismagilov; A. G. Sabirov; N. V. Balatenko; D. O. Zagvozkina; M. V. Galeev; I. A. Kiyasov (ABV-press, 2016)
Indications for the conservation of the skin flap over the tumor for potential offset of the operational access in aesthetically acceptable zone in patients with primary nodular breast cancer are discussed in the article. The survey results of 203 patients (T1-2N0-3M0) are analyzed. The study revealed that the risk factors affecting the skin flap involvement are the presence of the skin flattening as well as topographic and anatomical characteristics: tumor < 3 cm, located at a depth of < 0.46 ± 0.2 cm, tumor ≥ 3 cm located at a depth of < 1.66 cm. Based on the data the algorithm for immediate breast reconstruction from aesthetically acceptable zone for surgical oncologist is compiled.